Three stories in Kagulu, a Bantu language of Tanzania_2 - Petzell, Malin (University of Gothenburg, 2014)
The study comprises five stories told in the Bantu language Kagulu of Tanzania. The stories are available as sound recordings as well as glossed transcriptions. However, the transcriptions do not closely follow the sound recordings but have been normalised in cooperation with a native speaker.

Purpose:

The general aim is to document the Tanzanian minority language Kagulu.

This dataset contains two sound files with the stories "Being mischievous" and "The man and his wife". The files are in wave format. The recordings come with an original transcript made by a speaker and an interlinear transcript exported from Toolbox. Finally there is also a spreadsheet with metadata.

Studien omfattar fem berättelser på det tanzaniska bantuspråket kagulu. Berättelserna är tillgängliga som ljudinspelningar och annoterade transkriptioner. Transkriptionerna följer dock inte inspelningarna utan är normaliserade i samarbete med en talare.

Syfte:

Det övergripande syftet är att dokumentera det tanzaniska minoritetsspråket kagulu.

I detta dataset ingår två ljudfiler med berättelserna "Att vara elak" respektive "Mannen och hans hustru". Filerna är i wave-format. Till inspelningarna medföljer dessutom en originaltranskription gjord av en talare samt en interlinjär transkription som är exporterad från Toolbox. Slutligen ingår också ett kalkylblad med metadata.
Tre berättelser på kagulu, ett bantuspråk från Tanzania_2
Keywords: minority languages; minoritetsspråk; folklore; folksagor; translation; översättning; linguistics; lingvistik; linguistic analysis; lingvistisk analys; speech; tal (muntligt); literature; litteratur; preservation of cultural property; kulturminnesvård; minority groups; minoritetsgrupp; dialect; dialekt; Bantu languages; bantuspråk; Language and linguistics; Språk och lingvistik; Studies of Specific Languages; Studier av enskilda språk